Hawkinsinuria With Direct Hyperbilirubinemia in Egyptian-Lebanese Boy - El Khatib, Hassan; Asaad, Bilal; Zaylaa, Aisha; Awad, Farah; Sbeity, Mariam; Mneimneh, Sirin; Haber, Georges; Naja, Zeina; Rajab, Mariam (Frontiers in Pediatrics, 2019)
Tyrosinemia type III is the rarest type of tyrosinemia, because of a mutation in 4-OH-phenylpyruvate dioxygenase (HPD). This causes two different types of diseases with different modes of inheritance: tyrosinemia type III and hawkinsinuria. Hawkinsinuria is an autosomal dominant disease, which presents a failure to thrive and metabolic acidosis; however, the liver is not affected. P.A33T heterozygous mutation was reported by Tomoeda et al. to cause hawkinsinuria. This case report will present the first case of an Egyptian-Lebanese male who developed direct hyperbilirubinemia and was found to have tyrosinemia type III, due to elevated tyrosine levels in the blood and tyrosine derivatives in the urine, but genetic testing revealed a P.A33T heterozygous mutation, a cause of hawkinsinuria.